O grupo de Schrödinger em espaços de Zhidkov - Carvalho, Fábio Henrique de (2010)
This work is dedicated to the local and global well-possednes study of Cauchy s Problem associated to the nonlinear Schrödinger equation, to the initial data nonzero at infinity.